Konsep Islam Nusantara Dan Islam Berkemajuan Dalam Konteks Muhammadiyah Dan Nahdlatul Ulama - Ahmad, Lahmi; Julhadi, Julhadi; Ridwan, Muhammad; Mursal, Mursal; Ritonga, Mahyudin; Saputra, Riki (Institut Agama Islam Sumatera Barat Pariaman, 2025)
In this context, both Muhammadiyah and Nahdlatul Ulama have played a role in presenting a moderate and progressive Islam, which can make a significant contribution to social, economic and educational progress in Indonesia. However, the challenge of maintaining a balance between tradition and renewal, as well as in facing the challenges of globalization and radicalization, remains homework that must be completed. The aim of this research is to find out how Indonesian Islam and Islam are progressing in the context of Muhammadiyah and Nahdlatul Ulama. This research uses a qualitative approach with a library research method. Data was collected through literature studies related to the concepts of Nusantara Islam, Progressive Islam, as well as the role of Muhammadiyah and Nahdlatul Ulama in the development of Islam in Indonesia. The author examines various books, journal articles and relevant documents to analyze the role of these two Islamic organizations in facing challenges and realizing a moderate and progressive Islam. Islam Nusantara and Progressive Islam are two concepts that complement each other in the context of the development of Islam in Indonesia. Muhammadiyah and Nahdlatul Ulama, as two large mass organizations, have made significant contributions in realizing moderate, inclusive and progressive Islam. Despite facing various challenges, these two mass organizations continue to show their commitment to advancing society through education, da'wah and social programs. In the future, the challenges and opportunities that exist will test the ability of these two mass organizations to maintain the relevance of Islamic teachings in Indonesia's increasingly complex social and political life.